Effects of adrenaline, isoprenaline and histamine on transsinusoidal fluid filtration in the cat liver - Greenway, C. V. (1972)
1. Hepatic volume was recorded by a plethysmographic technique in cats anaesthetized with pentobarbitone. It has been shown previously that during an increase of hepatic venous pressure in this preparation, there is a maintained filtration of fluid from the sinusoids into the plethysmograph. The rate of this filtration is directly proportional to the increase in hepatic venous pressure. Infusions of drugs during this period of steady filtration provide a sensitive measure of the effects of the drugs on transsinusoidal fluid transfer. 2. Infusions of adrenaline, isoprenaline and histamine had no effect on the steady transsinusoidal filtration produced by an increased hepatic venous pressure. It is concluded that these agents do not change sinusoidal hydrostatic pressure by more than 1·5 mmHg (1 mmHg≡1·333 mbar) even though they alter hepatic arterial and portal flows. They do not change sinusoidal surface area by more than 20% and histamine does not change sinusoidal permeability. 3. The data are discussed in the light of current theories on the application of Starling's hypothesis to the liver sinusoids and to muscle capillaries. The postsinusoidal resistance appears to be very low in the liver and it does not increase during contraction of the capacitance vessels. The liver does not have presinusoidal sphincters, and closed sinusoids analogous to closed capillaries in skeletal muscle do not occur. The major factor controlling hepatic transsinusoidal fluid movements in the anaesthetized cat is hepatic venous pressure.